The Spiritual Psychological Robustness Scale (SPRS): A New Measure for Assessing Spiritual and Psychological Strength in the Context of Turkish Culture - Okan, Nesrullah; Eksi, Fusun (Springer, 2025)
This study introduces the spiritual psychological resilience scale (SPRS), a newly developed instrument designed to assess the integration of spiritual beliefs with psychological resilience in the Turkish context. The scale assesses the manner in which individuals draw upon spiritual resources to cope with adversity and maintain psychological well-being. Exploratory and confirmatory factor analyses identified a three-factor structure. Spiritual coping, spiritual beliefs and spiritual commitment collectively account for 55.01% of the variance. The scale exhibited robust internal consistency across all subscales, with Cronbach's alpha coefficients ranging from 0.785 to 0.854, thereby substantiating its reliability. Furthermore, the scale exhibited a notable negative correlation with spiritual contradiction, thereby substantiating its criterion validity. The SPRS provides a comprehensive instrument for evaluating spiritual and psychological resilience and is applicable to diverse populations. Future research should investigate its utility across different demographic and cultural groups, as well as its relevance to other psychological constructs such as depression and anxiety. This scale has the potential for use in counselling, educational and clinical settings, particularly for populations dealing with trauma and adversity.
Keywords: Spiritual robustness; Psychological resilience; Spiritual coping; Scale development; Turkish context